1997
DOI: 10.1901/jaba.1997.30-423
|View full text |Cite
|
Sign up to set email alerts
|

On the Relative Reinforcing Effects of Choice and Differential Consequences

Abstract: Research on the reinforcing effects of providing choice-making opportunities to individuals with developmental disabilities (i.e., allowing them to choose reinforcers or tasks) has produced inconsistent results, perhaps because the mechanisms underlying such effects remain unclear. Choice may produce a reinforcement effect because it is correlated with differential consequences (i.e., choice may increase one's access to higher preference stimuli), or it may have reinforcement value independent of (or in additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
106
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(124 citation statements)
references
References 25 publications
15
106
0
1
Order By: Relevance
“…In fact, other types of instructional arrangements may be more sensitive to the effects of choice on behavior. For example, in two studies in which a concurrent-operants arrangement was used to examine the effects of reinforcement choice, subjects consistently allocated more of their responses to the choice option than to the no-choice option (Brigham & Sherman, 1973;Fisher, Thompson, Piazza, Crosland, & Gotjen, 1997), suggesting that subjects preferred choices per se.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, other types of instructional arrangements may be more sensitive to the effects of choice on behavior. For example, in two studies in which a concurrent-operants arrangement was used to examine the effects of reinforcement choice, subjects consistently allocated more of their responses to the choice option than to the no-choice option (Brigham & Sherman, 1973;Fisher, Thompson, Piazza, Crosland, & Gotjen, 1997), suggesting that subjects preferred choices per se.…”
Section: Resultsmentioning
confidence: 99%
“…Providing choices to individuals with disabilities has been encouraged within interventions as a means to develop autonomy as well as being an important part of the normalization process (Fisher, Thompson, Piazza, Crosland, & Gotjen, 1997). A number of investigations have shown that allowing individuals to make choices between tasks or reinforcing consequences is an effective technique in both decreasing maladaptive behavior and increasing compliance to instructions (Powell & Nelson, 1997;Romaniuk et al, 2002).…”
Section: Choice Proceduresmentioning
confidence: 99%
“…In a study examining individuals' preference between choice and no-choice conditions, Fisher et al (1997) proposed that the decrease in problem behavior observed in a choice paradigm might be a function of increased access to preferred stimuli.…”
Section: Choice Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Por isso, o ensino do comportamento de escolher deve constituir-se objetivo fundamental nos programas educativos para pessoas com defi ciência intelectual severa ou profunda (Escobal & Goyos, 2008;Fisher, Thompson, Piazza, Crosland, & Gotjen, 1997).…”
unclassified